2021
DOI: 10.1038/s41401-021-00705-5
|View full text |Cite
|
Sign up to set email alerts
|

NADPH is superior to NADH or edaravone in ameliorating metabolic disturbance and brain injury in ischemic stroke

Abstract: Our previous studies confirm that exogenous reduced nicotinamide adenine dinucleotide phosphate (NADPH) exerts a neuroprotective effect in animal models of ischemic stroke, and its primary mechanism is related to anti-oxidative stress and improved energy metabolism. However, it is unknown whether nicotinamide adenine dinucleotide (NADH) also plays a neuroprotective role and whether NADPH is superior to NADH against ischemic stroke? In this study we compared the efficacy of NADH, NADPH, and edaravone in amelior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It participates in a variety of biochemical reactions as a hydrogen transmitter in vivo. Studies have confirmed that NADPH can resist oxidative stress and improve energy metabolism, so as to play a neuroprotective role in stroke [146]. NADPH oxidases (NOXs) have 7 kinds of subtypes.…”
Section: Nadph-and Nox-mediated Oxidative Stressmentioning
confidence: 99%
“…It participates in a variety of biochemical reactions as a hydrogen transmitter in vivo. Studies have confirmed that NADPH can resist oxidative stress and improve energy metabolism, so as to play a neuroprotective role in stroke [146]. NADPH oxidases (NOXs) have 7 kinds of subtypes.…”
Section: Nadph-and Nox-mediated Oxidative Stressmentioning
confidence: 99%
“…Surprisingly, we have previously found that i.v. NADPH can be well enriched in the brain and has dramatic therapeutic efficacy against ischemic encephalopathy [ 55 ]. There is a widespread belief that NADP + or NADPH must be generated by intracellular metabolism and cannot be transported from the extracellular space [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were exceptions, such as the “Regulation of Golgi to plasma membrane protein transport” pathway, which progressively decreased in expression in monocytes in CE, LV and SV stroke, a pathway shown to affect outcomes in experimental stroke [119]. Another example was “NADH oxidation” which peaked at 24 h in neutrophils in CE, LV and SV strokes and is known to play a role in experimental stroke [120]. There were few shared GO terms enriched in DEGs in whole blood CE, LV and SV strokes, likely related to the cellular heterogeneity of whole blood.…”
Section: Discussionmentioning
confidence: 99%